Small wars : their principles and practice - Callwell, C. E. (Charles Edward), Sir, 1859-1928 (University of Nebraska Press, 1996)
Originally published in 1896, Small Wars is an ambitious attempt to analyze and draw lessons from Western experience in fighting campaigns of imperial conquest. For the historian, Small Wars remains a useful and vital analysis of irregular warfare experiences, ranging from Hoche's suppression of the Vendee revolt during the French Revolution to the British wars against semi-organized armies of Marathas and Sikhs in mid-nineteenth-century India to the Boer War of 1899-1902. The military specialist discovers in Callwell lessons applicable to what today is called "low-intensity conflict." His message is clear, and it is relevant to current debates about conflicts as diverse as those in Bosnia, Somalia, and Vietnam. Technological superiority is an important, but seldom critical, ingredient in the success of low-intensity operations. An ability to adapt to terrain and climate, to match the enemy in mobility and inventiveness, to collect intelligence, and above all the capacity to "seize what the enemy prizes most," will determine success or failure. This reprint adds historical dimensions to the growing literature on unconventional conflict